2016
DOI: 10.3389/fonc.2016.00205
|View full text |Cite
|
Sign up to set email alerts
|

Key Players in Choline Metabolic Reprograming in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC), defined as lack of estrogen and progesterone receptors in the absence of protein overexpression/gene amplification of human epidermal growth factor receptor 2, is still a clinical challenge despite progress in breast cancer care. 1H magnetic resonance spectroscopy allows identification and non-invasive monitoring of TNBC metabolic aberrations and elucidation of some key mechanisms underlying tumor progression. Thus, it has the potential to improve in vivo diagnosis and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 70 publications
1
30
3
Order By: Relevance
“…In some of the metabolic ratios (PME/PDE and PME/Pi) a large variation among patients was observed, which is probably due to physiological differences in the heterogeneous patient group of our study including different kinds of tumors and different kinds of NAC treatment. It has been shown in several studies that estrogen and progesterone can be involved in activation of choline‐kinase . However, in this study no correlations were found among the metabolic ratios and ER status and PR status, which is probably due to the relatively low number of patients included.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In some of the metabolic ratios (PME/PDE and PME/Pi) a large variation among patients was observed, which is probably due to physiological differences in the heterogeneous patient group of our study including different kinds of tumors and different kinds of NAC treatment. It has been shown in several studies that estrogen and progesterone can be involved in activation of choline‐kinase . However, in this study no correlations were found among the metabolic ratios and ER status and PR status, which is probably due to the relatively low number of patients included.…”
Section: Discussioncontrasting
confidence: 75%
“…It has been shown in several studies that estrogen and progesterone can be involved in activation of choline-kinase. 16,37 However, in this study no correlations were found among the metabolic ratios and ER status and PR status, which is probably due to the relatively low number of patients included. A larger patient population is required for a more FIGURE 5 PME/PDE measured after spectral fitting of the individual 31 P spectra before (blue) and after (red) the first cycle of NAC arranged for the different pathological responses.…”
Section: Discussioncontrasting
confidence: 57%
“…Further understanding of these metabolic mechanisms in TNBCs will improve the development and implementation of Cho-based imaging techniques and advance novel therapeutics. 84 The tCho integral value has been reported to be increased in human studies with well-differentiated tumor types with high proliferative activity. 57 Tumors with very low proliferative activity, especially lobular cancers, show a scarce choline fraction with the MRS spectra.…”
Section: Determination Of Tumor Aggressiveness and Biological Behaviormentioning
confidence: 99%
“…Several human and experimental studies have shown that phosphatidylcholine metabolism is altered in TNBCs and phosphocholine levels are increased in TNBCs. Further understanding of these metabolic mechanisms in TNBCs will improve the development and implementation of Cho‐based imaging techniques and advance novel therapeutics …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Differences in the metabolism between various breast tumor subtypes and the complex molecular mechanism of cell proliferation and molecular heterogeneity of breast lesions may account for such behavior . Iorio et al have documented altered PtdCho metabolism during TN breast cancer progression . Baik et al showed a statistically significant correlation of Cho concentration with the rate constant k ep from DCEMRI experiment, on the basis of Cho being associated with active cell replication while the tumor growth requires active angiogenesis, resulting in leaky immature vessels …”
Section: In Vivo Mrs Methods In the Study Of Breast Cancer Metabolismmentioning
confidence: 99%